Construct validity of the Patient-Rated Wrist and Hand Evaluation questionnaire (PRWHE) for nerve repair in the hand. (April 2019) - Fonseca, Marisa C.Registro; Lalone, Emily; Claro da Silva, Natalia; Mendes Sugano, Raquel Metzker; Barbosa, Rafael I.; Marcolino, Alexandre M.; MacDermid, Joy C.
Abstract: Background: Many tools have been described for outcome assessment after nerve repair. The Patient-Rated Wrist and Hand Evaluation (PRWHE) have been shown to be valid for several hand conditions. Objectives: To explore the construct validity of the PRWHE in comparison to cold intolerance, pain and dysfunction questionnaires; the Rosén score and its subcomponents; and threshold sensibility, dynamometry and dexterity tests for nerve repair of the hand. Study design: Clinical measurement. Methods: Construct validity was analysed through Pearson's correlation coefficient in a convenience sample of 32 adult patients after long-term median and ulnar nerve repair. Results: The PRWHE total score was highly to moderately associated with the Disability of Arm, Shoulder and Hand ( r = 0.83), Cold Intolerance Symptom Severity ( r = −0.60) and McGill's Pain ( r = 0.58) questionnaires. In addition, it was correlated to motor ( r = −0.55) and sensor subdomains ( r = −0.56) of the Rosén score. Substantial to high associations were found for the motor, sensory impairment and dexterity test. Conclusions: The PRWHE was shown to be valid, based on construct validity, for patients with nerve repair of the hand. Highlights: PRWHE is a valid questionnaire to assess hand and wrist after nerve repair. PRWHE correlated with outcomes for motor and sensory, pain and functional domains. PRWHE was associated with DASH, CISS and MacGill questionnaires.